Sometimes You Have to Judge a Book by Its Cover: The Case of a Masquerading Pancreatic Mucinous Cyst. Issue 4 (27th April 2021) - Miller, John; Agostini-Vulaj, Diana; Howard, Victoria; Schoeniger, Luke; Kothari, Truptesh
ABSTRACT: Pancreatic cystic lesions are difficult to evaluate amid acute pancreatitis. Without previous pancreatic imaging, it is challenging to discern between pancreatic acute fluid collections and cystic neoplasms. We present a 29-year-old woman with acute pancreatitis and initial cross-sectional imaging suggesting a 2.8-cm cystic lesion in the body/tail of the pancreas. Endoscopic ultrasound completed 5 weeks after index presentation revealed findings worrisome for a cystic neoplasm, but fine-needle aspiration findings suggested lesion to be a pseudocyst (normal carcinoembryonic antigen and cytology, negative mucin stain).